L’apport de Lorenza Maranini dans le domaine des études flaubertiennes - Giorgetto Giorgi (Flaubert: Revue Critique et Génétique)
Lorenza Maranini (Bologna, 1909 - Pavia, 1998) published two important books on Flaubert’s works: Visione e personaggio secondo Flaubert e altri studi francesi (Padova, 1959) and Il ’48 nella struttura della “Éducation sentimentale” e altri studi francesi (Pisa, 1963). In the first book she brings to light how Flaubert’s prose offers a blend of visions: those altered by the characters’ passions and the narrator’s detached and neutral visions. In the second one she argues – and rejects – György Lukàcs’ famous theory developed in The Historical Novel (partially taken up by Jean-Paul Sartre in France and by Alberto Cento in Italy) according to which Flaubert ultimately supported reactionary theories in his Parisian novel.